A Pilot‐Scale Demonstration of Mobile Direct Air Capture Using Metal‐Organic Frameworks. (7th October 2020) - Sadiq, Muhammad Munir; Batten, Michael P.; Mulet, Xavier; Freeman, Christopher; Konstas, Kristina; Mardel, James I.; Tanner, Joanne; Ng, Derrick; Wang, Xingdong; Howard, Shaun; Hill, Matthew R.; Thornton, Aaron W.
Abstract: It is increasingly apparent that negative emissions technologies, such as direct air capture (DAC), are required as part of the technology mix for limiting global atmospheric temperature increase. For all DAC technologies, the requisite energy for regeneration of the separation media strongly influences the overall cost of the process and therefore directly influences their likely implementation. Herein, the results of a pilot‐scale demonstration of a new metal organic framework (MOF) based technology, Airthena, incorporated within a mobile unit for distributed deployment, are reported. Careful preparation of a MOF nanocomposite results in a CO2 ‐selective sorbent with fine‐tuned kinetic and thermodynamic properties. An optimum regeneration temperature of 80 ° C is achieved, along with strong repellence of water vapor during the adsorption process. Taken together, this demonstrator has delivered one of the lowest regeneration energy consumptions, 1.6 kWh kg‐CO2 −1 with output purity of 70–80%. This equates to an operational cost of 35–350 ton‐CO2 −1 depending on the source of regeneration energy. Over the duration of the pilot‐scale testing, the demonstrator captures a total of 8 kg of CO2 over 2680 cycles. Abstract : Airthena direct air capture (DAC) designed for CO2 capture from air can be part of the negative emissions technology mix to reduce global emissions. In the short term, the technology can provide a reliable source of renewable CO2 gas for everyday operation of small to medium scale industries, thereby significantly reducing their individual carbon footprint.